Isolated primary hydatid disease of thyroid presenting as a solitary nodule: A rare case report - Hoysal, Dileep Ramesh; Kulkarni, Srikanth (Indian Journal of Case Reports, 2019)
Echinococcosis is a significant health problem in endemic areas with a prevalence rate of 2–6%. Hydatidosis is reported in the liverin 70% of cases and lungs 15%, and rarely